Evaluation of different needle gauge blood collection sets (23G/25G) in aged patients - Rosada Adrian; Friedrich Katharina; Spieß Eileen; Prpic Monika; Müller-Werdan Ursula; Jahić Amir; Kappert Kai (Journal of Laboratory Medicine)
Aged patients are often characterized by difficult blood sampling conditions. Smaller needle gauge (G) may be beneficial for venous access and reduced pain perception, however, potentially at the expense of lower blood quality for laboratory measurements. We systematically compared two blood collection sets with different outer but equal inner diameters; different needle tips, and retract mechanisms in aged patients (Safety-Lok™, 23G, SL vs. UltraTouch™ Push Button, 25G, UT-PB) regarding clinical aspects and laboratory measurements.